2004
DOI: 10.1021/es049466y
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Biotransformation of 14C-Labeled 8-2 Telomer B Alcohol by Activated Sludge from a Domestic Sewage Treatment Plant

Abstract: This study investigated the biodegradation potential of 3-(14)C,1H,1H,2H,2H-perfluorodecanol [CF3(CF2)6(14)CF2CH2CH2OH, 14C-labeled 8-2 telomer B alcohol or 14C-labeled 8-2 TBA] by diluted activated sludge from a domestic wastewater treatment plant under aerobic conditions. After sample extraction with acetonitrile, biotransformation products were separated and quantified by LC/ARC (on-line liquid chromatography/accurate radioisotope counting) with a limit of quantification about 0.5% of the 14C counts applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
169
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(193 citation statements)
references
References 16 publications
(60 reference statements)
19
169
5
Order By: Relevance
“…Evidence for biotransformation of the FTOHs to the FTCAs and FTUCAs exists for both microbes (2,3,21) and mammals, both in vivo (40) and in vitro (38), and it likely occurs in all exposed organisms, including humans. Our data, therefore, suggest that further consideration of the toxicology of telomer acids is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for biotransformation of the FTOHs to the FTCAs and FTUCAs exists for both microbes (2,3,21) and mammals, both in vivo (40) and in vitro (38), and it likely occurs in all exposed organisms, including humans. Our data, therefore, suggest that further consideration of the toxicology of telomer acids is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [3] calculated the mass flux of PFCAs in the global transport processes and suggested that historical direct emissions from manufacture and consumer usages were the major contributors of PFCAs detected in the environment. However, the indirect contributions via the biodegradation and biotransformation of polyfluoroalkyl precursors and atmospheric oxidation have also been confirmed by model prediction [9], laboratory experiments [10,11] and environmental monitoring [12]. Laboratory systems utilizing microbialconsortium and animal models to study polyfluoroalkyl-precursor biotransformation provided insight to understand the extent of contributions of such precursors to PFCAs and PFSAs detected in the environment and biota.…”
Section: Introductionmentioning
confidence: 86%
“…Also, Wang et al [10] used trimethyl silyl (TMS) to increase the volatility of metabolites derived from an 8:2 FTCA biodegradation study in GC-MS analysis, and 7:3 FTCA was firstly recognized as the proposed structure of an unidentified peak.…”
Section: Derivatization Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect sources of PFOA and PFOS are photo-and microbial degradation of neutral precursors such as perfluorosulfonamides (FOSA), perfluorosulfonamidoethanols (FOSE), and FTOHs (D' Eon et al 2006;Ellis et al 2004;Wang et al 2005a;Wang et al 2005b). Because of their slow reaction process with hydroxyl radicals, atmospheric lifetimes were estimated~10−20 days for FTOH and~20−50 days for perfluoroalkane sulphonamide (FASA) in smog chamber studies (Ellis et al 2004;Martin et al 2006) and atmospheric residence time of more than 50 days for FTOHs in field studies (Piekarz et al 2007), which suggest they are subject to regional and long-range atmospheric transport, e.g., the Arctic and Antarctic (Dreyer et al 2009b;Stock et al 2007;Jahnke et al 2007b).…”
Section: Introductionmentioning
confidence: 99%